Dyslexia screening: a bibliometric analysis in mapping research patterns and emerging trends - Nik Zatul-Iffah N Mohd Nabil; Mohd Effendi Ewan Mohd Matore; Mohd Syazwan Zainal (Intelektual Pustaka Media Utama, 2026)
Dyslexia is a neurodevelopmental disorder that hinders reading, spelling, and writing abilities, creating challenges for academic success and necessitating early screening for timely intervention. This study presents a bibliometric analysis of global research on dyslexia screening from 2000 to 2023, using VOSviewer version 1.6.19 to analyze 839 publications from the Web of Science Core Collection (WoSCC). The findings reveal a growing interest in dyslexia screening, with a steady increase in both publications and citations. Key journals, such as Dyslexia and Journal of Learning Disabilities, are identified as central contributors to the field. Keyword analysis shows a focus on diagnostic tools and associated comorbidities, while collaboration patterns highlight strong research networks in Europe, the United States, and emerging contributions from Australia, Canada, and Brazil. However, the study also underscores the need for more inclusive and cross-regional collaborations to ensure the global applicability of screening tools. The implications of this study are significant, offering a roadmap for future research and emphasizing the importance of developing culturally sensitive and widely accessible dyslexia screening methods. This comprehensive analysis sets the stage for more targeted and impactful research and interventions in the field of dyslexia screening.